Phytochemical and Antiplasmodial Studies of Methanol Extract from Aerial Parts of Scadoxus multiflorus - Olaiya, Akeem Ayodele; Tijani, Tawakaltu Omolara; Garba, Dauda; Abdullahi, Sakynah Musa; Sule, Ibrahim Mohammed (Sciences of Phytochemistry, 2025)
Scadoxus multiflorus, a fleshy herbaceous plant with a large bulb, has been traditionally used in ethnomedicine for treatment of malaria, ulcers, cardiotonic activity and stimulant in debility. This study aimed to conduct phytochemical screening and evaluate the antiplasmodial activity of its aerial parts. The plant material was extracted with methanol using maceration process, and the crude extract was partitioned into hexane, chloroform, ethyl acetate, and butanol fractions. Qualitative phytochemical screening revealed the presence of tannins, flavonoids, alkaloids, terpenoids, steroids, saponins, phenols, and cardiac glycosides in the crude extract and fractions. Quantitative analysis revealed that phenolic compounds were the most abundant in the crude extract (198.32 mg/g), while alkaloids were the least (51.14 mg/g). The n-hexane fraction, however, had the highest tannin content (215 mg/g). Acute toxicity testing, following OECD 2008 guidelines, showed that the median lethal dose (LD₅₀) was greater than 5000 mg/kg, indicating the extract's safety. Antiplasmodial activity was evaluated using both suppressive and curative models in Plasmodium berghei-infected albino mice. The extract at 1000 mg/kg significantly suppressed parasitemia by 58.8% in the early infection (suppressive test) and reduced parasitemia by 61.8% in the established infection (curative test). Chloroquine, the standard drug at 5 mg/kg, produced higher parasite suppression (84.52%) and curative effects (84.50%) compared to the extract. The results suggest that the methanol extract of S. multiflorus aerial parts possesses antiplasmodial activity, supporting its traditional use in malaria management.